Idea del contrato: cincuenta años después (consideraciones previas a una definición del contrato) - García Amigo, Manuel (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
It is a question of verifying that, if with a conceptual scheme of the contract, based on the classic conception of Domat —who inspired the Civil Latin Codes: Frenchman, Spanish, Italian— and of Savigny —who inspired the German BGB—, there can be assumed the new contractual realities of the general conditions and of the improper clauses in consumers contracts: it comes near to the conclusion of the idea of a «three-dimensional» contract —of contract as juridical fact (declarations of will), as contractual relation and as norm/rules (or part of it) regulating that relation— it is better perceived and those modern phenomena are more fully explained, and of his legislative sequel: the partial nullity of the contractual rules/norm, as well as of the classic figures of the interpretation and of the integration of the contract.
Keywords: Contract; Efficiency of the contract; General conditions; Abusive clauses; Partial nullity; Integration; Contractual relation; Rules/contractual norm